Genetic parameters for medullated fiber and its relationship with other productive traits in alpacas. (20th December 2018) - Cruz, A.; Morante, R.; Gutiérrez, J. P.; Torres, R.; Burgos, A.; Cervantes, I.
Abstract : The alpaca fiber diameter (FD) varies from 18 to 36 μm, being the finer fiber categories highly appreciated. However, the alpaca fiber presents some limitations in the textile industry due to the high incidence of fiber medullation and diameter variability, both reduces the comfort feeling of the garments. Decreasing or even removing medullation could be a possible selection objective in alpaca breeding programs for increasing economic value of the alpaca fiber. Therefore, the present work aimed to estimate genetic parameters regarding medullation traits, as well as the genetic correlations with other economical important traits, to be able to select the appropriate criteria to reduce or remove medullation on alpaca fiber and help to reduce the prickle factor in the garments. The data was collected from 2000 to 2017 and belonged to the Pacomarca experimental farm. There were 3698 medullation records corresponding to 1869 Huacaya and 414 Suri genetic types. The fiber samples were taken from the mid side, and were analyzed in an OFDA 100 ® device. The traits analyzed were percentage of medullation (PM), medullated fiber diameter (MFD), FD, standard deviation of FD, greasy fleece weight as fiber traits; density, crimp in Huacaya and lock structure in Suri, head conformation, leg coverage as morphological traits; weaning weight and age at first calving as secondary and functional traits. Genetic parameters were estimated via a multitrait restricted maximum likelihood. The heritabilities for PM and MFD were 0.225 and 0.237 in Huacaya genetic type and 0.664 and 0.237 in Suri genetic type, respectively; heritabilities for other traits were moderate for productive and morphological traits, and low to moderate for secondary and functional traits. The genetic correlations PM–FD and MFD–FD were high and favorable in both genetic types, between 0.531 and 0.975; the genetic correlation PM–MFD was 0.121 in Huacaya and 0.427 in Suri. The rest of genetic correlations with other traits were in general moderate and favorable. The repeatabilities were 0.556 and 0.668 for PM, and 0.322 and 0.293 for MFD in Huacaya and Suri genetic types, respectively. As a conclusion, PM was identified to be a good selection criterion, probably combined in an index with FD to reduce prickling factor.